Tratamento e desfechos da persistência do canal arterial em recém-nascidos pré-termo extremo baixo peso com restrição de crescimento intrauterino: Estudo de coorte multicêntrico - Cunha, Thaís Sales Lemos da (2022)
Introduction: Intrauterine growth restriction (IUGR) is a morbidity commonly observed in preterm infants. The management of patent ductus arteriosus (PDA) is still controversial and it would be useful to identify newborns at high risk and with greater benefits from treatment of this condition. The aim of this study was to assess whether IUGR affects treatment and outcomes in preterm infants with PDA, when compared to eutrophic patients. Materials and methods: A retrospective cohort study, in which neonates diagnosed with PDA, gestational age (GA) between 22 and 33 weeks and 6 days, birth weight (BW) ≤ 1000g, born from 2012 to 2019, in 17 centers of the Brazilian Network on Neonatal Research (abbreviated as RBPN in Portuguese) were included. Exposure to IUGR was analyzed, and the frequencies of treatment and clinical complications were compared between the groups. Subsequently, exposure to IUGR, pharmacological treatment of PDA, and confounding factors in relation to the development of morbidities were evaluated. Results: 2205 patients with PDA were eligible: 531 with IUGR (24.08%) and 1674 (75.92%) eutrophic. In general, maternal risk factors were more prevalent in preterm infants with IUGR (82.1% x 57.4% p<0.001). Neonates with IUGR were less likely to undergo pharmacological (40.1% x 56.5%; p<0.001) and surgical (7.3% x 11.5%; p=0.022) treatment. In a second analysis, when considering IUGR exposure, pharmacological treatment of PDA and potential confounders that differed between groups (GA, BW, maternal risk factors, antenatal corticosteroid exposure), was observed a 53% reduction in death rate (OR 0.47, 95% CI 0.39 - 0.57), 40% reduction in bronchopulmonary dysplasia (BPD) (OR 0.59, 95% CI 0.42 - 0.82) and 30% reduction in periventricular leukomalacia (PVL) (OR 0.73 95% CI 0.55 - 0.98) with pharmacological treatment of PDA. Conclusion: Extremely low birth weight (ELBW) preterm infants diagnosed with PDA and IUGR had lower rates of pharmacological and surgical treatment when compared to eutrophic infants with PDA. On the other hand, pharmacological treatment in ELBW preterm newborns was associated with a reduction in the rate of death, BPD and PVL, suggesting the need for an individualized strategy for the therapeutic approach of PDA in this group of patients.